PENGARUH CURRENT RATIO DAN DEBT TO EQUITY RATIO TERHADAP RETURN ON EQUITY PADA PT BUMI SERPONG DAMAI, TBK PERIODE 2011– 2023 - Devi Apriliyani; Riski Dwi Nugroho (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This research aims to determine the influence of the Current Ratio and Debt To Equity Ratio partially and simultaneously on Return On Equity at PT Bumi Serpong Damai, Tbk for the 2011-2023 period. The research method used is a quantitative research method. The data used is secondary data in the form of financial reports of PT Bumi Serpong Damai, Tbk for the 2011-2023 period. The analytical methods used are descriptive analysis, classical assumption test, correlation coefficient, simple linear regression analysis, multiple linear regression analysis and hypothesis testing with the T test and F test using SPSS version 27. The results of this research based on the t test (partial) show that The current ratio has a t-count value of (-0.714) < t-table < (2.228) with a significance level of 0.492 > 0.05 so that partially the Current Ratio has no effect on Return On Equity, the Debt to Equity Ratio has a t-count value of (- 2.682) > t- table > (2.228) with a significance level of 0.023 < 0.05 so that partially the Debt To Equity Ratio has an effect on Return On Equity. Simultaneous research results between Current Ratio and Debt To Equity Ratio on Return On Equity show the value of F-count (4.528) > F-table (4.102) with a significance level of 0.040 < 0.05, so simultaneously Current Ratio and Debt To Equity Ratio have an effect on Return On Equity, while the coefficient of determination value is 37.0%, which means that the independent variables consist of the Current ratio and debt to equity ratio. Meanwhile, the remaining 63.0% is influenced by variables outside the research model.